Internalisasi Nilai-Nilai Religius Untuk Pembentukan Karakter Pada Pembelajaran IPA Siswa Kelas V SDN Karangasem II Surakarta - Sutono, Sutono, Prof. Dr. Abdul Ngalim, M.M, M.Hum, Dr. Sofyan Anif, M.Si (2016)
This research is motivated that the reality of life in the world of education, science learning is important. This is proved by the continuity in the learning of basic education to the upper secondary education. IPA is one of science to know the secrets of Nature that should be utilized as much as possible by humans. Learning science in this case the students of class V SDN Karangasem II Surakarta, in the context of fostering faith and piety do with the selection of instructional materials in accordance with the principles of faith and piety coaching and guidance to the science teacher of faith and piety. Thus, a science teacher in addition to teaching the IPA also teach the teachings of Islam and morals to all creatures created by God both animals and plants. Consider the reasons mentioned above, improving the quality of science teaching with the planting of Islamic values it is worth starting by providing a model of learning development starting from lesson plans, teaching materials, to the teaching strategies by extracting the values of religious in Islam. The results show that learning science-based integration of science and religion has been able to develop character values for students fifth grade students at SDN Karangasem 2 Surakarta. Keywords: science, religious values, character formation, students of class V SDN Karangasem II Surakarta